A novel approach to evaluate ELISA antibody coverage of host cell proteins—combining ELISA‐based immunocapture and mass spectrometry. (9th March 2020) - Pilely, Katrine; Nielsen, Solveig B.; Draborg, Anette; Henriksen, Maiken L.; Hansen, Søren W. K.; Skriver, Lars; Mørtz, Ejvind; Lund, Rikke R.
Abstract: Monitoring host cell proteins (HCPs) is one of the most important analytical requirements in production of recombinant biopharmaceuticals to ensure product purity and patient safety. Enzyme‐linked immunosorbent assay (ELISA) is the standard method for monitoring HCP clearance. It is important to validate that the critical reagent of an ELISA, the HCP antibody, covers a broad spectrum of the HCPs potentially present in the purified drug substance. Current coverage methods for assessing HCP antibody coverage are based on 2D‐Western blot or immunoaffinity‐purification combined with 2D gel electrophoresis and have several limitations. In the present study, we present a novel coverage method combining ELISA‐based immunocapture with protein identification by liquid chromatography–tandem mass spectrometry (LC–MS/MS): ELISA‐MS. ELISA‐MS is used to accurately determine HCP coverage of an early process sample by three commercially available anti‐ Escherichia coli HCP antibodies, evading the limitations of current methods for coverage analysis, and taking advantage of the benefits of MS analysis. The results obtained comprise a list of individual HCPs covered by each HCP antibody. The novel method shows high sensitivity, high reproducibility, and enables tight control of nonspecific binding through inclusion of a species‐specific isotype control antibody. We propose that ELISA‐MS will be a valuable supplement to existing coverage methods or even a replacement. ELISA‐MS will increase the possibility of selecting the best HCP ELISA, thus improving HCP surveillance and resulting in a final HCP profile with the lowest achievable risk. Overall, this will be beneficial to both the pharmaceutical industry and patient safety.